Biologisch-ökologische Untersuchungen über die Blattläuse der Unkraut- und Ruderalflora Berlins (Homoptera: Aphididae). - Schwarz, Ralph (Contributions to Entomology = Beiträge zur Entomologie, 1959)
In the years 1956 and 1957 the biology and ecology of the aphids of the weeds and ruderal plants were being investigated in the area of Berlin. - 1. The aphid species hibernating on weeds and ruderal plants were exclusively mono-respectively oligophagous. Their hosts during the winter in most cases were perennial plants which were found mainly in ruderal places. - 2. All aphid species investigated hatched by earlier in 1957 than in 1956. The reason for the high mortality of Myzodes persicae Sulz. in spring 1956 has been found in the fact that the phenology of the aphid (hatching date) and its host (budding) are not corresponding. The development of the population of Doralis fabae Scop, on Evonymus europaea L. iup to the taking-off was studied quantitatively. The result was the following: The increase of population in places hidden from the free access of parasites and predators is greater than in open places but it is vice versa with the decrease. The statement of Benett (1955) that Brachycaudus helichrysi Kalt, can hatch as early as autumn could be affirmed. - 3. Hibernation by virginogeniae in the open occured only in the mild winter of 1956/1957, not in the severe winter 1955/1956. - 4. For the spread of the apterae in ruderal and weed plant communities the sociological data of their hosts are of importance. - 5. The development of the aphid population in both years was studied by direct observation and by yellow water traps (Moericke traps). As a regard the proportion of alatae of the various species of the whole aphid flight showed the same succession of the maximum of alatae in both years: Brachycaudus helichrysi Kalt., Boralis fabae Scop., Aphidula nasturtii Kalt, and Brevicoryne brassicae L. While in 1956 the occurence of aphid colonies and the flight of alatae was corresponding, 1957 there was a discrepance between the (small) quantity of the whole population and the (great) number of alatae in the air. - 6. By direct observation and by catches of yellow water traps the occurence of gynoparae and males in the autumns precceding both years were compared. In autumn 1955 a stronger flight to the winter host was being stated than in autumn 1956. - 7. In the aphid colonies investigated the following predators and parasites appeared (in succession of their importance): Coccinellidae, Syrphidae, Braconidae and Chalcididae, Chrysopidae, Itonididae and Thrombidiidae. Their development was being watched by direct observation and by catches of yellow water traps (the latter was possible only with Syrphidae). The colonies of Doralis fabae on the winter hosts were decimated by Coccinellidae in most cases in 1956 and in all cases in 1957. While much fewer Syrphidae, Braconidae and Chalcididae appeared in 1957 than in 1956, the population of Coccinellidae was greater in 1957 than in 1956. The cilmax of the flight of the Syrphidae, Braconidae and Chalcididae in 1956 was in late summer after the depression of the aphid flight, whereas in 1957 there was no climax of flight. The balanced development of the aphids on hosts in ruderal places (in some distance from the crops) is of great advantage for the maintenance of a population of aphid predators and parasits.